Heart rate variability in obsessive compulsive disorder in comparison to healthy controls and as predictor of treatment response. (June 2022) - Olbrich, Hanife; Jahn, Ina; Stengler, Katarina; Seifritz, Erich; Colla, Michael
Highlights: Patients suffering from obsessive-compulsive disorder showed an elevated heart rate during the resting state compared to healthy controls. Responders differed from non-responders by an increased logarithmic High Frequency Heart Rate Variability Power, pointing toward a higher parasympathetic tone. Discriminative value of all Heart Rate Variability markers for differentiating response versus non-response was high with a sensitivity of 88% and a specificity of 57%. Abstract: Objective: Obsessive compulsive disorder (OCD) has a large impact on the quality of life of patients. It often takes years to get the right diagnosis and to receive treatment. Therefore, biomarkers that could inform the diagnostic process and provide information on response or non-response for first line treatment approaches are urgently needed. The aim of this study was to analyze whether (1) heart rate (HR) and heart rate variability (HRV) markers of the autonomous nervous system could distinguish between healthy controls (HC) and patients suffering from OCD and (2) HRV parameters additionally yield useful information to separate therapy-responders from non-responders. Methods: A fifteen-minute resting state ECG (electrocardiogram) was recorded from 51 unmedicated OCD patients before treatment and 28 HC. The function of the autonomic nervous system was assessed by using parameters of the HRV. Clinical Global Impression (CGI) scores served as baseline and outcome parameters following three to six months of therapy (cognitive behavioral therapy n = 18, selective-serotonin-reuptake-inhibitor n = 11 or combination n = 22). Differences between patients and HC and responders and non-responders were identified using analysis of covariance (ANCOVAs). Predictive values were calculated following binary regression modelling and receiver operating characteristics (ROC). Results: OCD patients revealed a significantly higher HR in comparison to HC. Although patients were thus characterized by increased sympathetic and decreased parasympathetic tone, treatment responders exhibited a larger High Frequency Power as a marker for increased parasympathetic activity at baseline. ROC-curves for OCD vs HC and R vs NR showed clinically relevant areas under curve (83%, 88% respectively). Conclusions: These results are in line with findings of increased sympathetic and decreased parasympathetic activity in OCD in comparison to healthy subjects. The findings further provide clinically useful information on treatment response in OCD. Significance: Results may facilitate the clinical use of electrophysiological markers in OCD.